(untitled) (Research, Society and Development, 2021)
This study aimed to verify the effect of light and heat on bleaching action of 40% hydrogen peroxide (Opalescence Boost PF – Ultradent, BR). Thirty-three bovine incisors were submitted to in-office dental bleaching and divided into three groups (n=11): CO group – control, no light or heat; CA group – heat with a hairdryer; LC group – light and heat with a photoactivation device. For this, a gingival barrier (OpalDam – Ultradent, SP, BR) isolated a circular area around the flatter region of the crown. Afterwards, the bleaching gel was applied for 15 minutes and repeated twice, totaling 45 minutes of application. For the CA and LC groups, the heat source was maintained during the application of the bleaching gel. Temperature was standardized in 5°C for both groups and monitored using a thermocouple inserted into the pulp chamber. The color measurement was performed before and after bleaching using a spectrophotometer. The inner margin of the isolated area of each dental crown was equivalent to the tip of the spectrophotometer (4 mm). Color change was verified by CIEDE2000 system (ΔE00). One way ANOVA and Tukey’s test were used to analyze data (p-values set to 5%). The values of ΔE00 were equal for LC (2,66±0,29) and CA (2,44±0,88), and both were higher than CO (1,31±0,37). Therefore, light does not play a fundamental role for in-office dental bleaching. Same dental bleaching outcomes are obtained using different heat sources.